Moving beyond financial remittances: The evolution of diaspora policy in post-conflict economies. (February 2020) - Williams, Nick
This article examines the role of institutional change in engaging the diaspora to invest in their home country. The article draws on in-depth interviews with key stakeholders in Bosnia & Herzegovina, Kosovo and Montenegro, all post-conflict economies which have experienced significant outward migration. This article shows that despite the importance attached to the diaspora in policy discourse, they are an under-utilised resource in economic and social development. While diaspora entrepreneurs have a strong emotional connection to their home country, they have faced numerous barriers upon returning due to unstable institutional environments. Many provide financial remittances but can remain isolated from entrepreneurial activity, and social remittances are limited due to the skills gained while in the host country. Institutional improvements are required if they are to be assimilated into the economy. The article concludes by providing a number of implications for institutional theory and policy.